Survival Strategy for Lokan Seekers in Paya Pasir Village, Kecamatan Marelan, Medan, Indonesia - Ramadani Lubis; Ichwan Azhari; Ratih Baiduri (Jurnal Antropologi Sumatera, 2019)
This study dealt with Survival Strategy for Lokan Seekers in Paya Pasir Village, Kec. Marelan, Medan, Indonesia. This situation explains that the number of women in poverty is still high. The high rate of poverty involving women certainly does not happen on its own, there are many things that must be explored and investigated and discussed about what factors make women and poverty as difficult to reduce and eliminate. The research used was qualitative research with an ethnographic approach. Spradley (1997: 3) argues that ethnography is the work of describing a culture. The main purpose of this activity is to understand a view of life from the perspective of the native population. In result, For parents, especially those who have a low income level, it should make children's education the first, because to improve the standard of living can only be done with education. Good children's education will produce changes in life. Besides that, a child should not be taught or supervised in fulfilling the family's economic needs, so that the child can be more focused in taking his education. With this education, a child can compete in the world of structural work, so as to reduce poverty as in the area of Paya Pasir Village.